The Hellenistic koine as a linguistic and ceramic concept - Laftsidis, Alexandros (Journal of Greek Archaeology, 2019)
The expanded, politically unified entity that resulted from the conquests of Alexander III facilitated the movement of people, products, and ideas in a way much easier and more effective than before. The governance of the vast and ethnically diversified Hellenistic kingdoms required the use of an accessible linguistic device, which we know as Hellenistic koine. This dialect of Greek, being a key component of cosmopolitan Hellenistic culture, played an important role towards the homogenisation of the vast Hellenistic world, becoming a lingua franca and allowing people of totally different cultural backgrounds to interact with each other formally and informally. Common cultural elements throughout the Hellenistic world, seem, on the surface, to extend beyond language to the area of material culture and, in particular, pottery. In fact, several scholars, including Werner Technau, Konstantina Gravani and Stella Drougou, have argued for a koine ceramic language characterised by the appearance of common pottery shapes, production methods, and decorative techniques throughout the Hellenistic world. In this paper, however, I argue that linguistic koine and ceramic koine are not parallel phenomena, as many researchers seem to accept, even though they arise from similar political and cultural developments. The former was at least originally imposed by the political administration of the Hellenistic kingdoms upon the people living in the Hellenistic world, while the latter reflects a bottom-up process. Hence, the issues I will be exploring below are the form of both the linguistic and ceramic ‘koinai,’ their origin, and their different formative processes.